A comparison of the mean arch dimensions of selected Filipino high school students with normal occlusion and the Unitek Arch Symmetry Chart - Galang, Maria Therese Sabater
The dental arch form, particularty the mandibular arch form has been regarded with utmost importance in retention and stability during orthodontic treatment. The use of guides in formulating arch wires has been a common practice in some orthodontic clinics and schools. The aim of this study was to determine if ther is a significant difference between the dimensions of the average arch form of selected Filipino high school students with normal occlusion and the Unitek Arch Symmetry Chart. Twenty five (25) our of 280 students were taken and the casts were measured using specific reference points. The mean of thesese measurements was computed and the dimensions were compared to the dimensions of the Unitek Arch Symmetry Chart by means of a t test with 0.05 level of significance. Results showed that the inter-canine width, inter 1st molar width, mean and total arch lengths of the study samples were significantly different from that of the Unitek Arch Symmetry Chart.
Keywords: Orthodontics; Dental arch